Hydrothermal Process to Prepare Novel Phase Titanium Sub-Oxide Ti6O11 from Nano Rutile Titanium Dioxide Particles with Different Autodave Reactors - Fahem, Mohanad Q.; Hassan, Thamir A.A. (Iraqi Journal of Science, 2022)
Hydrothermal process method using different dimensions reactors with volume 100 ml (homemade) was employed to prepare titanium sub-oxide Ti6O11, where one gram of TiO2 nanoparticles 30-50 nm and 3M (20 ml) of NaOH as suspension was used . The samples are characterized using X-ray diffraction, Raman spectroscopy, and Field Emission Scanning Electron Microscopy (FE-SEM). X-ray diffraction revealed the formation of sub- oxide titanium Ti6O11 of triclinic structure with Magneli phase, when the temperature applied was 363K for 9h.While FE-SEM showed uniform hierarchical structures with planar grass-like shapes. A novel phase has been found from rutile titanium.